Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Standar Akuntansi Pemerintahan, dan Penerapan Sistem Akuntansi Keuangan Daerah Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Halmahera Tengah - Maryani Sabtu; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
This study aims to determine how the influence of human resource competence, the application of government accounting standards, and the application of regional financial accounting systems on the quality of financial reports. This research is a type of quantitative research, with a total of 95 employees in the financial sector of the regional government of Central Halmahera as the sample in this study. The data collection method used a questionnaire distributed via Google Forms with a Likert scale, namely 1 strongly disagree, 2 disagree, 3 neutral, 4 agree, and 5 strongly agree. Based on the results of the study it is known that the human resource competency variable obtains a significance value of 0.029 <0.005 then H2 is accepted and H0 is rejected, the variable of application of government accounting standards obtains a significance value of 0.923 > 0.05 then H3 is rejected and H0 is accepted, the variable of application of the regional financial accounting system obtains significance value of 0.032 <0.05 then H4 is accepted and H0 is rejected. Based on this explanation, it can be concluded that the competence of human resources and the application of regional financial accounting systems have a partial effect on the quality of financial reports. On the other hand, the variable of applying accounting standards was found to have no partial effect on the financial statements.Keywords: Human resources, government accounting standards, financial accounting systems, quality of financial reports